2008
DOI: 10.1002/jcb.21724
|View full text |Cite
|
Sign up to set email alerts
|

Induction of hepatocyte growth factor expression by maleic acid in human fibroblasts through MAPK activation

Abstract: Carboxylic acids have various biological activities and play critical roles in cellular metabolic pathways such as the tricarboxylic acid (TCA) cycle. It has been shown that some carboxylic acids induce cell proliferation and production of cytokines or growth factors. However, there have been no reports on effects of carboxylic acids on hepatocyte growth factor (HGF) expression. In this study, we found that only maleic acid among various carboxylic acids examined markedly induced HGF production from human derm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…The MEK/ERK1/2 pathway phosphorylates the transcription factor cAMP response element binding protein (CREB), which translocates into the nucleus and induces the transcription of BDNF and IGF-1 [ 55 , 56 , 57 , 58 ]. Recent studies have demonstrated that AKT and ERK1/2 also stimulate VEGF expression via HIF-1α activation [ 59 ] and that HGF production is upregulated by the RhoA-PI3K/Akt-MEK/ERK1/2 signaling axis [ 60 , 61 ]. Alongside these findings, the expression of neurotrophic and growth factors such as BDNF, VEGF, IGF-1, and HGF was increased in ETH-MSCs ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The MEK/ERK1/2 pathway phosphorylates the transcription factor cAMP response element binding protein (CREB), which translocates into the nucleus and induces the transcription of BDNF and IGF-1 [ 55 , 56 , 57 , 58 ]. Recent studies have demonstrated that AKT and ERK1/2 also stimulate VEGF expression via HIF-1α activation [ 59 ] and that HGF production is upregulated by the RhoA-PI3K/Akt-MEK/ERK1/2 signaling axis [ 60 , 61 ]. Alongside these findings, the expression of neurotrophic and growth factors such as BDNF, VEGF, IGF-1, and HGF was increased in ETH-MSCs ( Figure S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…HGF gene transcription can be induced via several different intracellular signaling pathways, including MAPK and PI3K/Akt signaling pathways. In human fibroblasts, HGF expression induced by maleic acid requires activation of ERK and JNK, but not p38 MAPK [Motoki et al, 2008], whereas inflammatory cytokine IL‐1beta and IFN‐gamma‐induced HGF production in human fibroblasts requires activation of ERK and p38 MAPK but not of JNK [Takami et al, 2005]. In contrast, HGF production of human MSCs stimulated by LPS, or hypoxia depends on p38 MAPK activation but does not depend on increased ERK or JNK phosphorylation [Crisostomo et al, 2008].…”
Section: Discussionmentioning
confidence: 99%
“…Various stimulants induce HGF mRNA expression through MAPK activation [15,16]. Furthermore, gene expression of an angiogenic factor, cysteine-rich protein 61, was induced through RhoA and the p38 MAPK pathway in smooth muscle cells [19].…”
Section: Activation Of Mapks Up-regulates Apoptotic Cell-induced Hgf mentioning
confidence: 99%